1996
DOI: 10.1021/bi961995u
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of the Major Human AP-Endonuclease, a Multifunctional Protein,

Abstract: Abasic sites in DNA are generated either spontaneously or after removal of altered bases during the base excision repair process. These as well as 3' damaged ends of DNA at single-strand breaks induced by reactive oxygen species are repaired by AP-endonucleases. The major human AP-endonuclease (named APE-1) has two unrelated activities. It may function as an activator of c-Fos and c-Jun transcription factors and as a repressor of the parathyroid hormone (PTH) gene by binding to the negative Ca(2+)-response ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…Upregulation of Ape1/Ref-1 significantly potentiates the hypoxia-induced expression of a reporter construct containing the HIF-1-binding site (38), and Ape1/Ref-1 is thought to be critical in the linking of two coactivator proteins, CBP/p300 and SRC-1, to HIF-1␣ (10,18). Furthermore, Ape1/Ref-1 is found to be a component of protein complexes that binds to negative calcium response element (nCaRE) (65), Ku70(Ku86) (14), and heterogeneous nuclear ribonucleoprotein L (47) in the promoter of the parathyroid hormone (PTH) gene, the renin gene, and the Ape1/ Ref-1 gene itself, where it may downregulate the expression of these genes (26,41). Recent work suggests that Ape1/Ref-1 is acetylated by CBP/p300 both in vivo and in vitro, and acetylation stimulates binding to nCaRE in the PTH promoter, leading to downregulation of the PTH gene (6).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of Ape1/Ref-1 significantly potentiates the hypoxia-induced expression of a reporter construct containing the HIF-1-binding site (38), and Ape1/Ref-1 is thought to be critical in the linking of two coactivator proteins, CBP/p300 and SRC-1, to HIF-1␣ (10,18). Furthermore, Ape1/Ref-1 is found to be a component of protein complexes that binds to negative calcium response element (nCaRE) (65), Ku70(Ku86) (14), and heterogeneous nuclear ribonucleoprotein L (47) in the promoter of the parathyroid hormone (PTH) gene, the renin gene, and the Ape1/ Ref-1 gene itself, where it may downregulate the expression of these genes (26,41). Recent work suggests that Ape1/Ref-1 is acetylated by CBP/p300 both in vivo and in vitro, and acetylation stimulates binding to nCaRE in the PTH promoter, leading to downregulation of the PTH gene (6).…”
Section: Discussionmentioning
confidence: 99%
“…A role for APE1 in nCaREdependent transcriptional suppression was also observed for the human renin gene in chorio-decidual cells as a part of a response to elevated intra-cellular Ca 2 + levels (54) and for the BAX gene in gastric epithelial cells as a part of an elaborate response to Helicobacter pylori infection that involves APE1 acetylation and poly(ADP)ribose polymerase 1 (PARP1) (12). Interestingly, the upstream region of the APE1 promoter contains three nCaRE-like sequences, at least one of which (nCaRE-B2) appears to be bound by an APE1-containing protein complex that negatively auto-regulates gene expression (90). A follow-up analysis revealed that heterogenous nuclear ribonucleoprotein L (hnRNP-L) was a component of the nCaRE-B2 binding complex (113).…”
Section: Trans-acting Modulationmentioning
confidence: 99%
“…Transfection of HeLa S3 cells was carried out by electroporation (Izumi et al, 1996) because with this method the size of the vector does not signi®cantly aect the transfection eciency. About 1610 7 cells were trypsinized, washed twice and resuspended in 250 ml of ice cold Dulbecco's Phosphate buered saline.…”
Section: Assay For Transiently Expressed Reporter Genementioning
confidence: 99%